2013
DOI: 10.1089/ars.2012.4806
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Endothelial Cell Mitochondrial Bioenergetics in Lambs with Increased Pulmonary Blood Flow

Abstract: Aims: The mitochondrial dysfunction in our lamb model of congenital heart disease with increased pulmonary blood flow (PBF) (Shunt) is associated with disrupted carnitine metabolism. Our recent studies have also shown that asymmetric dimethylarginine (ADMA) levels are increased in Shunt lambs and ADMA increases the nitration of mitochondrial proteins in lamb pulmonary arterial endothelial cells (PAEC) in a nitric oxide synthase (NOS)-dependent manner. Thus, we determined whether there was a mechanistic link be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 56 publications
1
31
0
Order By: Relevance
“…This is in agreement with our recent studies in which we showed that asymmetric ADMA, an endogenous NOS uncoupler, induces eNOS mitochondrial redistribution and the disruption of mitochondrial bioenergetics through the nitration of carnitine acetyl transferase and the attenuation of carnitine homeostasis (16). However, ADMA induces eNOS mitochondrial translocation via the nitration-mediated activation of Akt1 and increased phosphorylation of eNOS at S617 and S1,177 (19).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This is in agreement with our recent studies in which we showed that asymmetric ADMA, an endogenous NOS uncoupler, induces eNOS mitochondrial redistribution and the disruption of mitochondrial bioenergetics through the nitration of carnitine acetyl transferase and the attenuation of carnitine homeostasis (16). However, ADMA induces eNOS mitochondrial translocation via the nitration-mediated activation of Akt1 and increased phosphorylation of eNOS at S617 and S1,177 (19).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, this correlates with an increase in lactate levels (14), suggesting that a glycolytic switch may also be induced in these lambs. Interestingly, these lambs also have decreased ATP levels (16), suggesting that the glycolytic switch is unable to maintain ATP demand. We did not observe a decrease in ATP in PAECs exposed to ET-1, nor have reductions in ATP been observed in PAECs isolated from patients with idiopathic pulmonary arterial hypertension (33).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is possible that this sequence could interact with the positively charged eNOS mitochondrial translocation loop located at aa 627-631 (RRKRK) (14). Furthermore, we have recently shown in an animal model of pulmonary hypertension associated with increased pulmonary blood flow that increases in ADMA correlates with increased activities of CHIP and Hsp70 (47) and increased translocation of eNOS to the mitochondrion (48). However, further studies will be required to determine whether Hsp70 and/or CHIP play a role in regulating eNOS translocation to the mitochondrion.…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%